2004
DOI: 10.1093/ageing/afh091
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine reduces cerebral blood flow in patients recovering from an ischaemic stroke

Abstract: Since caffeine is present in the diet of most patients recovering from an acute ischaemic stroke this effect may have adverse clinical consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…However, the rapid onset of headache provoked by HD in our patient implies significantly faster caffeine elimination that could be explained by rapid removal of caffeine by dialysis. It has been demonstrated that caffeine reduces CBF in normal individuals and in patients recovering from an acute ischemic stroke [8]. In our patient, the measured blood flow velocities using TCD were within normal range at the beginning and in the end of dialysis session, implying that there was no change in CBF during her dialysis treatment.…”
Section: Discussionsupporting
confidence: 47%
“…However, the rapid onset of headache provoked by HD in our patient implies significantly faster caffeine elimination that could be explained by rapid removal of caffeine by dialysis. It has been demonstrated that caffeine reduces CBF in normal individuals and in patients recovering from an acute ischemic stroke [8]. In our patient, the measured blood flow velocities using TCD were within normal range at the beginning and in the end of dialysis session, implying that there was no change in CBF during her dialysis treatment.…”
Section: Discussionsupporting
confidence: 47%
“…The CBF was reduced in widespread regions spanning primarily subcortical gray matter (thalamus, basal ganglia, hippocampus, and posterior cingulum) and isolated frontal, parietal, and occipital regions. Previous studies that have focused on the effects of caffeine on CBF have primarily used it in conjunction with a clinical cohort 29 or with a sensory stimulus 30 as part of the paradigm. It is thus difficult, from these preexisting studies, to ascertain direct effects of caffeine on the normal baseline neurophysiology.…”
Section: Resting Cerebral Blood Flowmentioning
confidence: 99%
“…This cerebral vasoconstriction is caused by caffeine‐induced blockade of adenosine receptors (Ragab et al. ; Addicott et al. ; Sasaki et al.…”
Section: Discussionmentioning
confidence: 99%